2012
DOI: 10.1371/journal.pone.0050687
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Tangles through Time? Opposing Direct and Indirect Effects of an Invasive Omnivore on Stream Ecosystem Processes

Abstract: Omnivores can impact ecosystems via opposing direct or indirect effects. For example, omnivores that feed on herbivores and plants could either increase plant biomass due to the removal of herbivores or decrease plant biomass due to direct consumption. Thus, empirical quantification of the relative importance of direct and indirect impacts of omnivores is needed, especially the impacts of invasive omnivores. Here we investigated how an invasive omnivore (signal crayfish, Pacifastacus leniusculus) impacts strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Based on results from the upstream site, we hypothesize that the crayfish may also have an indirect effect on leaf litter due to consumption of native invertebrates. Similar results were described for the crayfish P. leniusculus in Californian (USA) streams (Moore et al, 2012) & McIntosh, 2006), in which predators have an indirect effect on detrital food webs by suppressing the efficiency of leaf litter decomposition. However, our results from the downstream site suggest that indirect effects on leaf decomposition through the consumption of native invertebrates may change through time and invertebrates seem to learn how to avoid the crayfish as a predator.…”
Section: Discussionsupporting
confidence: 81%
“…Based on results from the upstream site, we hypothesize that the crayfish may also have an indirect effect on leaf litter due to consumption of native invertebrates. Similar results were described for the crayfish P. leniusculus in Californian (USA) streams (Moore et al, 2012) & McIntosh, 2006), in which predators have an indirect effect on detrital food webs by suppressing the efficiency of leaf litter decomposition. However, our results from the downstream site suggest that indirect effects on leaf decomposition through the consumption of native invertebrates may change through time and invertebrates seem to learn how to avoid the crayfish as a predator.…”
Section: Discussionsupporting
confidence: 81%
“…() found the predatory impacts of bullhead on G. pulex in a chalkstream caused a dramatic decline in detrital processing. Conversely, macroconsumers of detritus such as crayfish may decouple such a cascade, functionally replacing the more specialised shredders and thereby still creating availability of nutrients to pass to higher levels (Usio & Townsend, ; Vanni, ; Moore et al ., ), although crayfish effects are likely to be species‐ (Dunoyer et al ., ) and size‐dependent (Mancinelli, Sangiorgio & Scalzo, ). Our combined evidence from the mesocosms, gut contents and stable isotopes indicated that E. sinensis is also a significant consumer of terrestrial leaf litter, so, depending on comparative processing rates and the degree to which shredder populations are reduced, this invader could similarly decouple such a cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Omnivorous species (i.e. species that forage across trophic levels) are important for food web structure through their bridging of multiple trophic levels (Moore et al., ; Parkyn, Collier, & Hicks, ). Invasive omnivores can have disproportionate impacts on native communities via direct and indirect effects that cascade through the food web (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive omnivores can have disproportionate impacts on native communities via direct and indirect effects that cascade through the food web (e.g. Klose & Cooper, ; Moore et al., ). Indeed, some omnivorous species have the potential to act as detritivores, herbivores, predators or scavengers in different habitats, implying that habitat characteristics have a disproportionately strong influence on diet.…”
Section: Introductionmentioning
confidence: 99%